Autoregressive Distributed Lag Kurs Dan Ekspor Karet Remah Terhadap Pertumbuhan Ekonomi Indonesia - Nulhanuddin Nulhanuddin; Devi Andriyani (Jurnal Ekonomi Regional Unimal, 2020)
This study aims to determine the effect of short-term and long-term exchange rates and crumb rubber exports on the economic growth of Indonesia. The data used are secondary data for 39 years from 1980 to 2018 accessed on www.world.bank.wdi.data.bank.org, www.pertanian.go.id, www.bps.go.id, and www.bps.go.id. The data analysis method used is the Autoregressive Distributed Lag (ARDL) approach with the help of EViews 10 software. The results show that the economic growth is stationary at the level and exchange rate and exports of stationary crumb rubber at the first difference level and have cointegration in the long-term relationship. The test results in the short-term analysis of the exchange rate have a positive and significant effect, and exports have a positive but insignificant effect on economic growth, while in the long run, the exchange rate has a negative effect but insignificant, and exports have a positive but insignificant effect on the economic growth of Indonesia. Keywords:economic growth, exchange rates, exports and the ARDL approach.